Central nervous system compromise in primary Sjögren's syndrome (2002)
Central nervous system (CNS) involvement in primary Sjögren’s syndrome (SS) is poorly understood, and its frequency as well as its manifestations are subjects of controversy. The current study was undertaken to determine the prevalence and the clinical and immunogenetic characteristics of CNS compromise in a well defined group of patients with primary SS. In this retrospective study, patients fulfilled the European classification criteria. Among 120 patients with primary SS, 3 (2.5%) had CNS compromise (multiple sclerosis–like illness, complicated migraine, and optic neuritis with epilepsy). The CNS involvement coincided with the onset of sicca symptoms in 1 case. All 3 patients carried the human leukocyte antigen (HLA) DQB1*0303 allele and tested positive for anti-Ro antibodies, but not for anti-cardiolipin antibodies. Although rare, CNS compromise in primary SS can be the presenting manifestation of the disease in a few cases, and may be severe and varied.